2021
DOI: 10.1177/10105395211019857
|View full text |Cite
|
Sign up to set email alerts
|

Delays in the Pathway to Cancer Diagnosis in Samoa: A Qualitative Study of Patients’ Experiences

Abstract: Cancer is a leading cause of death in Samoa, with cancer patients presenting late and experiencing poor outcomes. Barriers to early diagnosis are complex, and cultural factors play an important part. This qualitative study explored the barriers to cancer diagnosis in Samoa through semistructured interviews conducted with 19 Samoan patients. Thematic data analysis was informed by socioecological theory and yielded 4 themes: knowledge and beliefs about cancer; pain as a trigger for health care–seeking behavior; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The improved cancer awareness achieved through the community outreach education sessions resonates with the acknowledged importance of taking a grassroots approach to reaching underserved and/or geographically remote communities ( Northington et al , 2011 ). The lack of improvement reported around understanding the risk factors and cancer symptoms is consistent with previous research that has suggested cultural norms and beliefs that cancer is a western illness are acting as barriers to raising community awareness ( Cuesta-Briand et al, 2021a , b ). This suggests the need to draw in community partners such as traditional healers, chiefs and church leaders to support multiple strategies that address these misconceptions to increase depth of community knowledge.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The improved cancer awareness achieved through the community outreach education sessions resonates with the acknowledged importance of taking a grassroots approach to reaching underserved and/or geographically remote communities ( Northington et al , 2011 ). The lack of improvement reported around understanding the risk factors and cancer symptoms is consistent with previous research that has suggested cultural norms and beliefs that cancer is a western illness are acting as barriers to raising community awareness ( Cuesta-Briand et al, 2021a , b ). This suggests the need to draw in community partners such as traditional healers, chiefs and church leaders to support multiple strategies that address these misconceptions to increase depth of community knowledge.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, data from a WHO pilot study conducted with Samoan cancer patients found that many had relied on traditional medicine pre-diagnosis and that lack of trust in the healthcare system resulted in delays to seeking diagnosis and treatment (WHO, 2016, Insight into the experiences of patients seeking healthcare in Samoa, unpublished data). A more recent study with Samoan cancer patients corroborates these findings highlighting the importance of cultural barriers to early detection ( Cuesta-Briand et al , 2021a ). Churches in Samoa play a central role in Samoan culture and village life making churches an appropriate place for health promotion ( Holmgaard, 2019 ).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations